2008
DOI: 10.1097/01.hp.0000291943.50516.d0
|View full text |Cite
|
Sign up to set email alerts
|

CONCENTRATIONS OF 226Ra, 232Th, AND 40K IN THE SOILS OF BANGALORE REGION, INDIA

Abstract: Abstract-Several

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 14 publications
1
9
1
Order By: Relevance
“…Generally, all gamma dose rates were 30-80 times higher than the Norwegian average of 0.073 mGy h À1 and the world average of 0.058 mGy h À1 given by UNSCEAR, 2,26 as well as higher than those obtained for different reference sites worldwide. [29][30][31] However, results were comparable and confirmed the previous Fen Complex measurements obtained by Dahlgren, 32 Heincke et al, 15 and IFE. 20 Significant differences (p ¼ 0.0005) were found between some of the investigated sites.…”
Section: Gamma Dose Ratessupporting
confidence: 84%
“…Generally, all gamma dose rates were 30-80 times higher than the Norwegian average of 0.073 mGy h À1 and the world average of 0.058 mGy h À1 given by UNSCEAR, 2,26 as well as higher than those obtained for different reference sites worldwide. [29][30][31] However, results were comparable and confirmed the previous Fen Complex measurements obtained by Dahlgren, 32 Heincke et al, 15 and IFE. 20 Significant differences (p ¼ 0.0005) were found between some of the investigated sites.…”
Section: Gamma Dose Ratessupporting
confidence: 84%
“…Substantial work associated with the evaluation of the radioecological situation in 238 U and 232 Th deposit regions and in vicinity of mines has been performed in several regions such as Brazil, Australia, Europe, USA and Canada. [4][5][6][7][8] Some studies have shown various pathways of radionuclide and metal leaching from rocks and soil, as well as their transportation and concentration of hazardous decay products into the water, plants and animals in different degrees. 7,[9][10][11][12] It has also been shown that radionuclides could be present as radioactive particles.…”
Section: Environmental Impactmentioning
confidence: 99%
“…Table 2. Absorbed gamma dose rates in cities from different parts of the world compared with those obtained in the present study City D (nGy h -1 ) Bangalore, India [15] 117 (61-202) Csongrad, Hungary [14] 38 Debrecen, Hungary [14] 24 Faisalabad, Pakistan [16] 73 (62-79) Istanbul, Turkey [17] 49 (15-71) Palic, Serbia [13] Horgos, Serbia [13] Belgrade, Serbia [18] Alkharje, Saudi Arabia [19] 36 32 60 (25-90) 24 (15-30) Tafila, Jordan [20] 40(22-63) Tripoli, Libya [21] 23 (20-24) Windhoek, Namibia [22] 56 (41-70) Zacatecas, Mexico [23] 45 (28-67) Zahedan, Iran [24] Subotica,this study 158 (16-300) 32 It can be seen that the mean value of the gamma dose rate observed in the present study (32 nGy h -1 ) lies within the values reported worldwide. It is comparable with those reported for the cities of Palic and Horgos [13], which are close to Subotica.…”
Section: Resultsmentioning
confidence: 61%